From Natural to Artificial Intelligence - Algorithms and Applications 2018
DOI: 10.5772/intechopen.81623
|View full text |Cite
|
Sign up to set email alerts
|

Formative E-Assessment of Schema Acquisition in the Human Lexicon as a Tool in Adaptive Online Instruction

Abstract: This chapter presents a comprehensive method of implementing e-assessment in adaptive e-instruction systems. Specifically, a neural net classifier capable of discerning whether a student has integrated new schema-related concepts from course content into her/his lexicon is used by an expert system with a database containing natural mental representations from course content obtained from students and teachers for adapting e-instruction. Mental representation modeling is used to improve student modeling. Implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
0
9
0
2
Order By: Relevance
“…Moreover, the studies using NSN have been able to identify limitations in the knowledge structures of students, relating to each individual's level of academic development in terms of the subject they are learning. Morales-Martínez, Mezquita-Hoyos et al (2018) noted that students who did not achieve passing grades on the computational usability course had fractured knowledge schemata at the end of the course. Morales-Martinez, Angeles-Castellanos et al (2020) reported similar data in their cognitive diagnostic study on the structure and organization of the human anatomy knowledge schema amongst first-year medical students.…”
Section: Constructive Cognitive Evaluation Of Knowledge Schemata Learned During An Academic Coursementioning
confidence: 99%
“…Moreover, the studies using NSN have been able to identify limitations in the knowledge structures of students, relating to each individual's level of academic development in terms of the subject they are learning. Morales-Martínez, Mezquita-Hoyos et al (2018) noted that students who did not achieve passing grades on the computational usability course had fractured knowledge schemata at the end of the course. Morales-Martinez, Angeles-Castellanos et al (2020) reported similar data in their cognitive diagnostic study on the structure and organization of the human anatomy knowledge schema amongst first-year medical students.…”
Section: Constructive Cognitive Evaluation Of Knowledge Schemata Learned During An Academic Coursementioning
confidence: 99%
“…Finalmente, el modelo de evaluación constructiva-cronométrica, en conjunto con su herramienta EVCOG, pueden permitir la exploración de nuevas áreas del proceso de aprendizaje que nos permitan ampliar nuestra comprensión de la naturaleza cognitiva de este proceso. Por ejemplo, nuevas aplicaciones de esta visión se están extendiendo a la exploración de los mecanismos cognitivos del escaneo visual de textos (véase Morales-Martínez, Mezquita-Hoyos et al, 2018) y comienzan a brindar información sobre los procesos cognitivos que subyacen a la apropiación del conocimiento en la mente de los estudiantes.…”
Section: Conclusionesunclassified
“…Aquí se propone y se ilustra el uso integrado de las herramientas provenientes de la ciencia cognitiva relacionada con la memoria y el aprendizaje humano, la aplicación de avances de la ciencia computacional y la tecnología para innovar y complementar los sistemas de evaluación del aprendizaje académico en niveles de educación superior. En particular, se ilustran algunos de los resultados obtenidos con el uso de un sistema cognitivo de orientación constructiva/cronométrica llamado «EVCOG» (evaluador cognitivo), que permite al maestro empoderar sus juicios de valor sobre el conocimiento internalizado en el estudiante (López, Morales, Hedlefs, González y Moreno, 2015;Morales-Martínez y Santos-Alcántara, 2015;Morales-Martínez, López-Ramírez y Velasco-Moreno, 2016;Morales-Martínez, López-Ramírez, Castro-Campos, Villarreal-Treviño y Gonzales-Trujillo, 2017;Morales-Martínez, Mezquita-Hoyos, González-Trujillo, López-Ramírez y García-Durán , 2018).…”
Section: Introductionunclassified
“…These changes are specific indicators that the student has experienced a learning process due to the academic experiences during the course (Morales-Martinez et al, 2021). In addition, the NSNs technique has made it possible to identify difficulties in the integration of information in a unified schema in students with low academic performance and in beginners, when learning a topic (Morales-Martínez, Mezquita-Hoyos, et al, 2018;Morales-Martinez, Angeles-Castellanos, et al, 2020;Morales-Martinez, Lopez-Perez, et al, 2020;Urdiales-Ibarra et al, 2018). Furthermore, Morales-Martinez, Angeles-Castellanos, et al (2020) applied this technique to explore the formation of the anatomy schema in medicine students and they discovered that other factors could affect schema configuration in the minds of students, for example the difficulties associated with academic performance, the level of academic development of students, and the emphasis and distribution of the topics to be reviewed.…”
Section: Advances In the Cognitive Assessment Of Knowledge Constructionmentioning
confidence: 99%
“…The NSNs can provide information on the effectiveness of corrective learning strategies. Using this tool, Morales-Martinez, Mezquita-Hoyos, et al (2018) observed that engineering students who did not achieve passing grades in a computational usability course could integrate the knowledge schema in this subject after attending a remedial course. Bearing in mind that NSNs are very useful for assessing several aspects of learning, Morales-Martinez, Trejo-Quintana, et al (2021) used this technique to explore the cognitive properties of knowledge acquisition on human cognition in psychology students.…”
Section: Advances In the Cognitive Assessment Of Knowledge Constructionmentioning
confidence: 99%